Solve the equation.

$3^{2 x-1}=6^{x} 3^{1-x}$

Solution

VerifiedIs given the equation

$\begin{aligned} 3 ^ { 2 x - 1 } = 6 ^ { x } \cdot 3 ^ { 1 - x } \end{aligned}$

Since $6=2\cdot 3$, $6 ^ { x } = ( 2 \cdot 3 ) ^ { x } = 2 ^ { x } - 3 ^ { x }$ (product rule for exponential) then the equation can be written as

$\begin{aligned} 3 ^ { 2 x - 1 } = 2 ^ { x } \cdot 3 ^ { x } \cdot 3 ^ { 1 - x } \equiv \frac { 3 ^ { 2 x - 1 } } { 3 ^ { x } \cdot 3 ^ { 1 - x } } = 2 ^ { x } \end{aligned}$

Using the product and quotient rule for exponential in the left side of the equation, we have that

$\begin{aligned} 3 ^ { 2 x - 1 - x - ( 1 - x ) } = 2 ^ { x } \Rightarrow 3 ^ { 2 x - 2 } = 2 ^ { x }\\ \Rightarrow \frac { 3 ^ { 2 x } } { 9 } = 2 ^ { x } \Rightarrow \frac { 9 ^ { x } } { 9 } = 2 ^ { x } \Rightarrow \frac { 9 ^ { x } } { 2 ^ { x } } = 9\\ \Rightarrow ( 9 / 2 ) ^ { x } = 9 \end{aligned}$

where we have used the product and quotient rules and the power rule to write $3 ^ { 2 x } = \left( 3 ^ { 2 } \right) ^ { x } = 9 ^ { x }$. Using now the equality rule for logarithm choosing as base $b = 9 / 2$ result

$\begin{aligned} \log _ { 9 / 2 } ( 9 / 2 ) ^ { x } = \log _ { 9 / 2 } 9 \end{aligned}$

Now, if we use the power rule its result

$\begin{aligned} x = \log _ { 9 / 2 } 9 \end{aligned}$

## Create a free account to view solutions

## Create a free account to view solutions

## Recommended textbook solutions

#### Thomas' Calculus

14th Edition•ISBN: 9780134438986 (11 more)Christopher E Heil, Joel R. Hass, Maurice D. Weir#### Calculus: Early Transcendentals

9th Edition•ISBN: 9781337613927 (3 more)Daniel K. Clegg, James Stewart, Saleem Watson#### Calculus

6th Edition•ISBN: 9781465208880 (1 more)Karl J. Smith, Magdalena D. Toda, Monty J. Strauss## More related questions

1/4

1/7